Permacul(SU+RE) designing a sustainable and regenerative agricultural eco-park through permaculture - Diquit, Joseph S.
As the impacts of global challenges worsen, the call for more sustainable developments strengthens. However, developments should not only be sustainable, they should also be regenerative. With this, the thesis titled, PERMACUL(SU+RE) Designing a Sustainable and Regenerative Agricultural Eco-park through Permaculture seeks to integrate the permaculture principles in the landscape design of Faraon Integrated Farm to enhance its sustainability and regenerative capacity, as Quirino aims to develop its only farm tourism-registered site. To achieve its goal, a series of analyses and programming was conducted to identify the areas where permaculture can be incorporated. As a result, a permaculture-based landscape design of a sustainable and regenerative agricultural eco-park with a closedloop system was developed. The eco-park is divided into six (6) permaculture zones, arranged according to the amount of attention it needs, consisting of areas chosen and designed based on the twelve (12) permaculture principles. In addition to this, various technologies, practices, and techniques were incorporated into the design such as intercropping, use of natural farming inputs, vermicomposting, rainwater harvester & catchment, and utilization of renewable sources of energy to improve its sustainability and regenerative capacity. By imitating the Earth’s natural processes and relationships found in nature, permaculture was able to create a sustainable and regenerative development to provide food, fiber, and energy to people. This thesis showcases its potential in solving the problems that the world is currently facing.